Click Chemistry in Human Cancer Research - Baihong ZHANG; Hongyun YUE (Zhongliu Fangzhi Yanjiu)
As one of the typical bioorthogonal chemistry reactions, click chemistry joins molecules similar to “Lego”. Bioorthogonal click chemistry is used to modify cancer cells, design antitumor drugs, delivery drugs, manipulate immune cells, and help preclinical evaluation. Click chemistry provides a promising approach for discovering molecules and targeting cancer in cancer research.